Fiqhī views on bayʾwa salaf and qarḍ-based Islamic banking deposit accounts in Malaysia - Mahadi Ahmad; Riaz Ansary (ISRA International Journal of Islamic Finance, 2017)
Purpose: Islamic banks are obliged to carry out transactions that only comply with Islamic commercial laws. Malaysia has been championing the Sharīʿah-based banking system, and so, continuous improvement on the compliance level of the institutions offering Islamic financial services is key to its global recognition in this industry. One of the issues that can affect deposit products is existence of a sale contract and loan facility in one transaction. Famous prophetic tradition prohibits this. Hence, this paper aims to examine the linkage between bayʿwa salaf (combination between a sale contract and loan in one transaction) and deposits accounts in Malaysia. Design/methodology/approach: The subject matter of this paper is one that is researchable within library-based research. It is on this premise the research used the non-empirical qualitative research methodology. It used inductive method of analysis of both Islamic and policy documents on Islamic banking in Malaysia. Literature from Islamic jurisprudence, websites of some of the Islamic banks in Malaysia and relevant resolutions from the Shariah Advisory Council of Central Bank of Malaysia were consulted. Findings: Based on the methodology mentioned above, the researchers arrived at the following findings: that, although there is no juristic disagreement about the prohibition of bayʿwa salaf, disagreement, however, occurs in results of some contracts. The most notable area of agreement on the existence of bayʿwa salaf is when there is express stipulation of sale or rendering of service and express or implied stipulation of loan alongside of the sale or service rendering. In an organized reversed tawarruq, the use of these deposits by the banks is regarded as loan from the depositors to the banks, who will soon put the money into sale that will generate profit to be divided between the banks and their depositors. However, this study finds that this is not bayʿwa salaf prohibited by the prophetic tradition. Originality/value: The originality of this topic is proven by the new banking regulation regime of Malaysia, which compels Islamic banks to guarantee all deposits under them. As Islamic banks carry out their banking activities through trading, there is need to conduct a research such as this. This is to examine whether Islamic banks' unilateral use of depositors' funds in non-investment accounts which is translated, constructively, as loan from the depositors to Islamic banks amounts to bayʿwa salaf before the future tawarruq. Here there is loan and sale, which is the tawarruq. Hence, the need to do this research.
Keywords: 330; Fiqhī; Bayʿwa salaf; Tawarruq; Deposit accounts